Amlodipine-induced gingival overgrowth - Triveni M; Rudrakshi C; Mehta D (Wolters Kluwer Medknow Publications, 2009)
Gingival overgrowth represents an over-exuberant response to a variety of local and systemic conditions. Certain anticonvulsants, immuno-suppressive drugs and a number of calcium channel blockers have been shown to produce similar gingival overgrowths in certain susceptible patients. Amlodipine is a comparatively new calcium channel blocker and has been used with increasing frequency in the management of hypertension and angina. Although amlodipine is considered as a safe drug, very rarely it may induce gingival overgrowth also. A rare case of amlodipine-induced gingival overgrowth has been reported herein in a 50-year-old female patient. The treatment aspect included Phase-1 therapy, substitution of the drug, the surgical excision and the maintenance and supportive therapy resulting in excellent clinical outcome.